From Flawed to Flourishing: Reshaping the Nigerian Curriculum for Sustainable National Development - Adeoye, Moses Adeleke; Mahmud, Musa Aremu; Ehindero, Ronke Elizabeth; Ajape, Rasheedat Oladunni; Yahaya, Ajoke Kudirat; Jolaoye, Joshua Durotoye (Journal of Education Action Reseach, 2023)
The Nigerian education system plays a crucial role in shaping the nation's future. However, over the years, there have been concerns about the effectiveness and relevance of the curriculum in preparing students to face rapidly changing global challenges. This research aims to explore the weaknesses within the current Nigerian curriculum and propose strategies to reshape it to drive sustainable national development. It is a comprehensive and systematic literature review, a critical step to thoroughly understand the challenges within Nigeria's curriculum and identify potential improvement strategies. This research allows for a comprehensive synthesis of scholarly articles, governmental reports, and educational publications, establishing a strong foundation for subsequent methodologies. The study begins by analyzing the current state of the Nigerian curriculum, highlighting its limitations and shortcomings. It delves into how the curriculum inadequately addresses critical skills and competencies needed by the 21st-century workforce, such as critical thinking, problem-solving, creativity, and digital literacy.The study emphasizes the need for continuous evaluation mechanisms and feedback to ensure the effectiveness of the modified curriculum. Regular assessments and monitoring systems should be implemented to measure the impact of curriculum changes and identify areas for improvement. By addressing these deficiencies and integrating relevant and practical skills, the curriculum can better prepare students to face future challenges.